Paralympic movement in Malaysia: The achievement of high-performance para sports - Abdullah, Nagoor Meera; Govindasamy, Mohan; Zaharudin, Megat Shahriman; Nair, Subramanian Raman (Journal Sport Area, 2021)
The article elaborates on the achievement of the Malaysian athletes with disabilities locally and also in international scenes. Malaysian athletes start to participate in international competition since 1962, and local games had been organized back in 1982 with the introduction of the Paralympic Games. The article also illustrates the medal achievement where Malaysian contingent achieved a total of 1700 medals at the ASEAN Para Games from 2001-2017. In FESPIC and Asian Para Games, a total of 582 medals was won from the year 1982-2018. At the FESPIC and Asian Youth Para Games, a total of 189 medals won from the year 2003-2017. The highest achievement came from the Paralympic games as Malaysian won 11 medals in total from the year 1962-2016. More need to be done to establish para sports in Malaysia with the support of every parties including the government and the media.